Sociodemogrphic Influence on Quality of Life in Caregivers of Chronic Dissease Care - Maria Prieska Putri Panglipur Ati; Febrina Secsaria Handini; Devina Rahmasari; Ristofel Krisna Amadea (Indonesian Journal of Global Health Research, 2025)
Chronic illnesses in elderly make them less able to meet their own needs independently and therefore rely on informal caregiver to help them manage their health. Informal caregivers have different demographic characteristics that impact their resilience and coping strategies, leading to a deterioration in quality of life. Objectives to analyse the sociodemographic factors that affect informal caregiver’s quality of life of elderly with chronic diseases. Methods: This study was conducted using non-experimental, cross-sectional design. The population consisted of 137 caregivers who care for the elderly with chronic disease with simple random sampling method of 109 respondents. Analysis of the data using logistic regression. Research showed that the majority of elderly caregivers had the good quality of life (49.54%), 44.95% had the moderate quality of life, and 5.5% had the low quality of life. The variable that influenced the quality of life of elderly caregivers is the caregiver experience, with p-value of 0.022 and it was the most influential factor in caregiver quality of life. The community health worker can provide education to families that impact on improving their quality of life.